Transthyretin Cardiac Amyloidosis - novel and emerging treatments - Francisco Pinto Dias (2021)
Transthyretin cardiac amyloidosis was until recently considered an untreatable disease. However, this underdiagnosed pathology experienced a surge in research interest with multiple novel treatments, including several first-in-class drugs rapidly approaching the final stages of investigation, with tafamidis and patisiran already approved by the European and American regulators. Novel drugs include small molecule stabilizers, gene silencing drugs, amyloid fibril disruptors, and monoclonal antibodies This review aims to capture a comprehensive picture of the current and upcoming therapeutic options for cardiac transthyretin amyloidosis, to ascertain if any of these drugs gather the necessary evidence to become the staple of transthyretin cardiac amyloidosis management and to identify relevant questions yet to be answered by currently available evidence.